Being as Breath, Vapor as Joy: Using Martin Heidegger to Re-read the Book of Ecclesiastes - Shuster, Martin (Journal for the study of the Old Testament, 2008)
This article is a philosophical re-examination of Ecclesiastes using the work of Martin Heidegger, particularly his early work in Being and Time. Heidegger's focus on death, temporality, and history provides a powerful and compelling framework for understanding these same themes in Ecclesiastes. In elaborating these philosophical motifs and correspondences, this article proposes that ‭לכה‬ should be understood as an analog to Heidegger's concept of Geschichtlichkeit (historicity). If ‭לכה‬ is understood as such, then most of the traditionally puzzling terms in Ecclesiastes (e.g. ‭םלעה‬, ‭למע‬, ‭החמש‬) can be made sense of using the aforementioned philosophical framework. This framework additionally shows that Ecclesiastes (like Being and Time) cannot be understood as a proto-existentialist text.